Minimally invasive surgery total knee arthroplasty is less popular, but the prosthesis designed specifically for MIS provides good survival and PROMs with a minimum follow-up of 10 years - Toyoda, Shinya (J Orthop Surg Res, 2021)
BACKGROUND: The concept of minimally invasive surgery (MIS) was introduced in total knee arthroplasty (TKA) in the late 1990s. The number of MIS TKAs has clearly decreased in recent years. An implant designed specifically for MIS TKA has been used all over the world, but there are no reports of long-term postoperative results. The purpose of this study was to characterize long-term clinical results with a minimum follow-up of 10 years. METHODS: This retrospective study included 109 consecutive patients with 143 NexGen CR-Flex prostheses, which are MIS tibial component prostheses designed specifically for MIS TKA. Twelve-year survival analysis was performed using Kaplan-Meier method. Revision surgery for any reason was the endpoint. Long-term clinical and radiographic results of 74 knees (55%) in 60 patients with more than 10 years of follow-up were analyzed. RESULTS: The cumulative survival rate of the single-radius posterior-stabilized TKA of 74 knees was 94.7% (95% confidence interval, 90–99%) at 12 years after surgery. Seven knees (9%) required additional surgery during the 10-year follow-up because of periprosthetic infections. Mean postoperative Knee Society knee score and functional score were 91 and 74 points, respectively. There were no cases of prosthesis breakage, polyethylene wear, or aseptic loosening of the prosthesis. CONCLUSION: The prosthesis designed specifically for MIS TKA is associated with good survival and clinical results with a minimum follow-up of 10 years, even though MIS TKA has become less popular. LEVEL OF EVIDENCE: III